STUDIES ON THE SEASONAL VARIABILITY IN THE SEDIMENT CHARACTERISTICS OF SELECTED PERENNIAL PONDS IN KANYAKUMARI DISTRICT, TAMIL NADU, INDIA. - K.Mary Rasmi; H.Mary Helen (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study investigates the seasonal fluctuations in sediment properties, specifically temperature, pH, EC, organic carbon, nitrogen, phosphorous, magnesium, calcium and potassium, across five perennial ponds in Kanyakumari district from February 2022 to January 2023. The findings demonstrated considerable seasonal variations in sediment characteristics caused by climate and human activity. During the pre-monsoon season, high concentrations of EC, Mg and Ca, were reported, owing to evaporation and nutrient concentration in the sediment. The monsoon season saw increasing pH, N, P, and K levels due to agricultural runoff and leaching from nearby fields, but dilution effects reduced other parameters such as EC and Ca. After the monsoon, water levels stabilized and runoff was reduced, resulting in moderate concentrations of most parameters, while K, Mg, N, and Ca were found slightly higher. Pond-specific differences revealed the impact of land-use practices, with Pond II accumulating the most nutrients due to agricultural runoff. These findings highlight the necessity of knowing seasonal dynamics and land-use influences in order to create effective solutions for sustainable pond management and sediment quality enhancement.